2010
DOI: 10.1186/1752-0509-4-133
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of metabolism with age and lifestyle in Antarctic seals: a case study of systems biology approach to cross-species microarray experiment

Abstract: BackgroundThe metabolic transformation that changes Weddell seal pups born on land into aquatic animals is not only interesting for the study of general biology, but it also provides a model for the acquired and congenital muscle disorders which are associated with oxygen metabolism in skeletal muscle. However, the analysis of gene expression in seals is hampered by the lack of specific microarrays and the very limited annotation of known Weddell seal (Leptonychotes weddellii) genes.ResultsMuscle samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Despite these improvements, sequence-based resources are still lacking for many non-model species such as marine mammals, hampering molecular understanding of unique adaptations and physiology. Only a handful of marine mammal genomes have been sequenced, annotation remains a challenge, and few transcriptomes are available [ 15 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these improvements, sequence-based resources are still lacking for many non-model species such as marine mammals, hampering molecular understanding of unique adaptations and physiology. Only a handful of marine mammal genomes have been sequenced, annotation remains a challenge, and few transcriptomes are available [ 15 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four genes ( PRKCA , PLCB4 , ROCK1 , MAPK10 ) in the Wnt signaling pathway were also present in the candidate aquatic adaptation gene list ( P = 0.007, Fisher’s exact test) ( Supplementary Table S6 ). Altered expression of genes associated with the Wnt pathway has been implicated in metabolic and structural transformation of Weddel seal skeletal muscle from a strictly terrestrial lifestyle as a pup to an aquatic lifestyle adapted for deep dives as adult animals 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, recent evidence has shown that the amount and type of lipids act as important initial regulators of myoglobin in diving mammals (De Miranda Jr. et al, 2012) with some indication of secondary regulation by activity level and calcium signaling (Kanatous et al, 2008b, 2009; Ptitsyn et al, 2010). In comparative animal studies, an increase of n− 3 PUFAs or a high n− 3 to n− 6 ratio of fatty acids was shown to prompt increases in calcium transport and calcium absorption in PUFA-deficient rats (Kruger and Horrobin, 1997; Weiss et al, 2005).…”
Section: Fatty Acids As Regulatory Signalsmentioning
confidence: 99%
“…These constraints demand that the Antarctic divers be more tightly regulated with respect to their oxygen utilization; they must complete a dive cycle and find a breathing hole before their oxygen stores are depleted. Previous research has illustrated how these and open water divers are uniquely adapted to their environment and how energy is conserved even at the molecular level (Burns, 1996 ; Burns et al, 1998 ; Kanatous et al, 1999 , 2001 , 2002 , 2008a , b ; Burns et al, 2005 , 2007 ; Clark et al, 2006 , 2007 ; Noren et al, 2008b ; Ptitsyn et al, 2010 ; Trumble et al, 2010 ; Ponganis et al, 2011 ; Williams et al, 2011 ). For example, studies of adult Weddell seals, harbor seals ( Phoca vitulina ) and Steller sea lions ( Euematopias jubatus ) have revealed that their muscle adaptations to maintain a lipid based aerobic metabolism under the hypoxic conditions associated with breath-hold diving include: (1) an increased aerobic capacity (or one that is matched to routine levels of exertion), (2) a reliance on fatty acid catabolism for aerobic ATP production, (3) enhanced oxygen storage and diffusion capacity, and (4) a reduced dependency on blood-borne oxygen and metabolites (e.g., decreased capillary density) compared to terrestrial mammals (Davis et al, 1991 ; Davis and Kanatous, 1999 ; Kanatous et al, 1999 , 2001 , 2002 ).…”
Section: Oxygen and Divingmentioning
confidence: 99%
See 1 more Smart Citation